Living in the end times through popular culture: An ultra-realist analysis of The Walking Dead as popular criminology. (December 2018) - Raymen, Thomas
This article provides an ultra-realist analysis of AMC's The Walking Dead as a form of 'popular criminology'. It is argued here that dystopian fiction such as The Walking Dead offers an opportunity for a popular criminology to address what criminologists have described as our discipline's aetiological crisis in theorizing harmful and violent subjectivities. The social relations, conditions and subjectivities displayed in dystopian fiction are in fact an exacerbation or extrapolation of our present norms, values and subjectivities, rather than a departure from them, and there are numerous real-world criminological parallels depicted within The Walking Dead 's postapocalyptic world. As such, the show possesses a hard kernel of Truth that is of significant utility in progressing criminological theories of violence and harmful subjectivity. The article therefore explores the ideological function of dystopian fiction as the fetishistic disavowal of the dark underbelly of liberal capitalism; and views the show as an example of the ultra-realist concepts of special liberty, the criminal undertaker and the pseudopacification process in action. In drawing on these cutting-edge criminological theories, it is argued that we can use criminological analyses of popular culture to provide incisive insights into the real-world relationship between violence and capitalism, and its proliferation of harmful subjectivities.